Two-step separation for enriching phenols and esters from base-catalyzed depolymerization of sorghum stalk. (15th April 2022) - Li, Zhan-Ku; Li, Xuan-Lan; Yan, Hong-Lei; Yan, Jing-Chong; Lei, Zhi-Ping; Ren, Shi-Biao; Wang, Zhi-Cai; Kang, Shi-Gang; Shui, Heng-Fu
Highlights: Base-catalyzed depolymerization of sorghum stalk was conducted. The suitable condition for total ESs yield was 280 °C with CaO/sorghum stalk ratio of 7:10 g/g. Catalytic reactivity of bases for biomass increase in the order: Na2 CO3 < NaOH < CaO. Phenols and esters were effectively separated with extraction and column chromatography. The concentration of enriched phenols and esters were up to 92% and 99%, respectively. Abstract: Base-catalyzed depolymerization of sorghum stalk using Na2 CO3, NaOH, and CaO was performed to afford methanol-soluble portion, and then extraction together with column chromatography was employed for enriching phenols and esters. The maximum total yield (ca. 53 wt%) of extract solutions 1–5 (ES1 –ES5 ) was acquired at 280 °C with the equal mass of CaO and sorghum stalk. According to gas chromatograph/mass spectrometer analysis, phenols and esters are the predominate products. The phenols obtained from Na2 CO3 -catalyzed depolymerization of sorghum stalk mainly are methoxylphenols, while those obtained from NaOH and CaO-catalyzed depolymerization are dominated by alkylphenols, suggesting that NaOH or CaO plays an important role in demethoxylation during biomass depolymerization process. Phenols, methyl alkanoates/benzenecarboxylates, and dimethyl alkanedioates were roughly enriched into ES1, ES3, and ES5 via sequential extraction with petroleum ether (PE), PE, and ethoxyethane, respectively. By the following column chromatographic separation of ES1 and ES3, alkylphenols and guaiacols were mainly enriched into PE/CS2 (4:3)-eluted fractions with maximum concentration of 92.2% and 92.1%, respectively. Saturated and unsaturated methyl alkanoates were isolated in concentration of near 100% by elution with PE/CS2 (9:1) and PE/CS2 (4:3), respectively. Extraction combined with column chromatography as two-step separation provides a promising approach for enriching phenols and esters from biomass-derived liquids.